Ethnomedicinal Study and Phytochemistry Analysis of Antihypertensive and Anticholesterol Plants in Sukaharja Village, Lebak Regency, Banten Province, Indonesia - Rindita, Rindita; Sherley , Sherley; Dewantara, Muhammad Alifian; Akhmal, Muhammad Nur (SEAMEO BIOTROP, 2025)
Medicinal plants are still used by people to treat many diseases, such as to lower cholesterol levels and hypertension. In Sukaharja Village, Lebak Regency, Banten Province, Indonesia, for example, the Baduy tribe still believe in practicing traditional medication. The village location is far away from the nearest health facilities. This ethnomedicinal study was conducted in the year 2023 by applying a quantitatively descriptive method. Data were collected by interviewing several respondents selected by purposive and snowball sampling methods. The list of plants was then verified by field observation, followed by species authentication, and use value (UV) calculation. Fresh samples of plants were made into simplicia and underwent phytochemical screening, including a TLC test, in a laboratory. From 50 respondents, we obtained information on 21 plant species used to lower cholesterol levels and for treating hypertension. The highest UV of plants used to lower cholesterol levels were Peperomia pellucida (0.56) and Annona muricata (0.52), while for treating hypertension were A. muricata (0.60), followed by Allium sativum (0.56). All of the plants used contained flavonoids, and selected plants examined by TLC test were revealed to be similar to quercetin. Traditional medication practices need to be preserved, which is as important as conserving medicinal plants that are precious biodiversity in Indonesia.